2020
DOI: 10.9734/jpri/2020/v32i3230930
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Isolation and Identification of Multidrug Resistant Pseudomonas aeruginosa from Wound Specimen

Abstract: Background: Pseudomonas aeruginosa is a clinically important pathogenic microbe in hospitalized patients. It is a major cause of mortality and morbidity having a number of mechanisms that make it antibiotic resistant. Considering the dearth of antimicrobial drugs to treat infection with this pathogen, it has become a necessity to open up new arena for treatment with this organism. Recently, there has been an up rise in the number of multidrug resistant pathogenic strains of Pseudomonas aeruginosa. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In P. aeruginosa, resistance mechanisms such as decreased permeability, expression of efflux pumps, target modifications and production of inactivating enzymes have all been described (Mesaros et al, 2007). In particular, production of extendedspectrum beta-lactamases and carbapenemases have been described, including metallo-beta-lactamases (Mesaros et al, 2007;Sacha et al, 2008;Ríos et al, 2018;Muddassir et al, 2021). Since these enzymes use zinc, which seems to be a valuable cofactor to hydrolyze beta-lactams, instead of serine in their active sites, they confer resistance to all beta-lactam antibiotics except aztreonam, while not being degraded by currently available beta-lactamase inhibitors (Sacha et al, 2008;Behzadi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In P. aeruginosa, resistance mechanisms such as decreased permeability, expression of efflux pumps, target modifications and production of inactivating enzymes have all been described (Mesaros et al, 2007). In particular, production of extendedspectrum beta-lactamases and carbapenemases have been described, including metallo-beta-lactamases (Mesaros et al, 2007;Sacha et al, 2008;Ríos et al, 2018;Muddassir et al, 2021). Since these enzymes use zinc, which seems to be a valuable cofactor to hydrolyze beta-lactams, instead of serine in their active sites, they confer resistance to all beta-lactam antibiotics except aztreonam, while not being degraded by currently available beta-lactamase inhibitors (Sacha et al, 2008;Behzadi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of P. aeruginosa in the wounds of patients at the Dschang District Hospital is 26.1%. P. aeruginosa is one of the most common pathogens in chronic wounds, and its ability to form resistant biofilms and several virulence factors that allow the establishment in host tissue, including pyocyanin has been documented [ 29 ]. This result corroborates the work done by Raizman et al, who reported the presence of P. aeruginosa in an infected wound [ 4 ].…”
Section: Discussionmentioning
confidence: 99%